Game-Based Training Model: Does It Improve Fundamental Badminton Young Athletes' Skills? - Eka Fitri Novita Sari; Nofi Marlina Siregar; Sigit Nugroho; Lala Septem Riza; Masnur Ali; Novri Asri (CV. FOUNDAE, 2025)
Background: The application of game models in badminton for young athletes is considered very appropriate. Game models incorporate training elements suitable for young athletes, who are still in a developmental stage that requires play, so that training can be maximized, as athletes feel more relaxed and have more fun in the program. Aims: The research aims to examine the effectiveness of the game model in improving young athletes' badminton skills. Methods: This study used a quantitative descriptive quasi-experimental design. The research design used in this study was “The One Group Pretest Posttest Design” with no control group. Results: The Wilcoxon test in Table 3 above shows that the pretest and posttest scores for badminton skills were significantly different (p < 0.05). Thus, the game model is efficacious in improving athletes' badminton skills. Conclusion: The game model applied in this study demonstrates high effectiveness in improving young athletes' badminton skills. Therefore, the researcher recommends using a game-based training model to improve young athletes' badminton skills. Implementing game-based training models can significantly enhance the development of young badminton athletes. By integrating play-oriented activities into training, coaches can create a more engaging and motivating environment that aligns with children's developmental needs. This approach not only improves technical and tactical skills in badminton but also promotes enjoyment, reduces training stress, and fosters long-term athlete participation.